Designing Of Computer Network In Cisco Packet Tracer Software - R.G.Rakhimov; A.A.Juraev (Peerian Journals Publishing, 2024)
This article presents the Cisco Packet Tracer software interface and its capabilities, the tasks of existing devices in the software interface and their analysis, the creation of a computer network project "Building №1 of the Namangan Engineering-Construction Institute" using this software, and the classification of costs for the project. Designing a network with the help of this program provides many conveniences to users, including time saving, low cost, and low labor consumption
Keywords: Cisco Packet Tracer; Ethernet; switch